Old‐growth forest structure in a low‐productivity hypermaritime rainforest in coastal British Columbia, Canada. Issue 5 (16th May 2021) - Hoffman, Kira M.; Starzomski, Brian M.; Lertzman, Ken P.; Giesbrecht, Ian J. W.; Trant, Andrew J.
Abstract: Dendrochronological analyses were conducted across a gradient of productivity and soil drainage quality characterizing four vegetation types in a low‐productivity hypermaritime (perhumid) temperate rainforest on the Central Coast of British Columbia, Canada. We examined the structure, composition, and stand dynamics of trees growing in 400 m 2 plots located in blanket bog, bog woodland, bog forest, and zonal forest vegetation types. We sampled over 2500 trees and 1500 seedlings and saplings and our dendrochronological reconstruction of six tree species revealed establishment ages extending to 660 A.D. (1350 yr). All forest plots contained numerous old trees (>250 yr) and the zonal forest and bog forest vegetation types contained significantly taller trees and also had the greatest amount of suppressed, shade‐tolerant tree species. The bog woodland vegetation type contained more seedlings and saplings than the other three vegetation types combined. The bog forest vegetation type had the highest density of dead standing trees (~530 per hectare). Blanket bogs contained an open structure with very few old trees (>250 yr). Significant differences in the ages of trees existed between forested vegetation types and the more open blanket bog vegetation type. Several trees exceeded 1000 yr in age and were situated in lower‐productivity bog forest and bog woodland sites. We found no evidence of widespread tree cohort establishment, indicating that small‐scale disturbances such as individual tree mortality and gap‐forming dynamics are likely the most frequent disturbance in the study area.